A Case Report of Neonatal Pediculosis: A Simple Challenge, yet Complex - Viveka Santhosh Reddy Challa; Soundarya Mahalingam; Kamalakshi Bhat (Mashhad University of Medical Sciences, 2020)
Background: Neonatal pediculosis is a problem the magnitude of which has not been estimated; however, it is regarded as a diagnostic challenge and becomes one of the management challenges for which there are very few managementoptions in terms of age, gestation, and the potential effects of drug toxicity. Case report: Here, we report a case of preterm who developed pediculosis capitis in the neonatal intensive care unit following contact with the mother during kangaroo mother care (KMC). She was successfully treated with a combination of topical extra virgin coconut and olive oil. Other radical treatments could not be administered due to cultural barriers. Conclusion: Furthermore, maternal lice were treated with 1 % permethrin, and the KMC re-initiated. For a successful outcome, the education of the mother was equally important. The neonate was found to be free of lice on follow-up. Therefore, it is concluded that in neonatal pediculosis, topical oils are safe alternatives where drug toxicity is a constraint.